Investigating demand for biofortified seeds in developing countries. Issue 1 (18th May 2015) - Birol, Ekin; Asare-Marfo, Dorene; Karandikar, Bhushana; Roy, Devesh; Diressie, Michael Tedla
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore farmer acceptance of a biofortified staple food crop in a developing country prior to its commercialization. The paper focuses on the hypothetical introduction of a high-iron pearl millet variety in Maharashtra, India, where pearl millet is among the most important staple crops. Design/methodology/approach – A choice experiment is used to investigate farmer preferences for and trade-offs among various production and consumption attributes of pearl millet. The key pearl millet attributes studied include days it takes pearl millet to mature, color of the roti (flat bread) the grain produces, the presence of high-iron content (nutritional attribute), and the price of the pearl millet seed. Choice data come from 630 pearl millet-producing households from three purposefully selected districts of Maharashtra. A latent class model is used to investigate the heterogeneity in farmers' preferences for pearl millet attributes and to profile farmers who are more or less likely to choose high-iron varieties of pearl millet. Findings – The results reveal that there are three distinct segments in the sample, and there is significant heterogeneity in farmer preferences across these segments. High-iron pearl millet is valued the most by larger households that produce mainly for household consumption and currently have lower quality diets. Households that mainly produce for market sales, on the other hand, derive lower benefits from consumption characteristics such as color and nutrition. Research limitations/implications – The main limitation of the study is that it uses a stated preference choice experiment method, which suffers from hypothetical bias. At the time of implementing this study biofortified high-iron pearl millet varieties were not yet developed, therefore the authors could not have implemented revealed preference elicitation methods with real products and payment. Originality/value – The method used (stated preference choice experiment method) is commonly used to value non-market goods such as environmental goods and products that are not yet in the market. It's application to agriculture and in developing countries is increasing. As far as the authors know this is the first choice experiment implemented to investigate farmer/consumer preferences for biofortified crops. The study presents valuable information for development and delivery of biofortified crops for reducing micronutrient deficiencies.